ATTRACTIVENESS OF MUNICIPALITIES IN MINAS GERAIS STATE FOR THE INSTALLATION OF FOREST-BASED COMPANIES/Atratividade dos municípios de Minas Gerais para a instalação de empresas de base florestal - Pereira Silva, Eliandra; Marques, Ricardo Tayarol; Coelho Junior, Luiz; Coimbra Borges, Luís Antônio (Informe GEPEC, 2024)
This paper measured the attractiveness of municipalities in the state of Minas Gerais (MG) for projects in the steel, cellulose and paper, furniture, energy and wood panel industry segments. A questionnaire was used to construct an index of attractiveness of the forestry sector for each municipality. As a result, it was found that 40% of the municipalities presented “average” or higher attractiveness. The mesoregions with the greatest potential for forestry development were the Belo Horizonte Metropolitan region, Southwestern Minas and Zona da Mata. The steel and cellulose and paper segments found attractive factors in 74.08% and 72.79% of the municipalities, respectively. It was concluded that the methodology applied showed how close a location was to meeting the characteristics of forest-based industries. It is expected to encourage future research and influence strategic planning for the expansion of the forestry sector across the country. Este trabalho mediu a atratividade de municípios do estado de Minas Gerais (MG) para projetos nos segmentos de siderurgia, celulose e papel, móveis, energia e painéis de madeira. Por meio de um questionário, foi construído um índice de atratividade do setor florestal para cada município. Como resultado, verificou-se que 40% dos municípios apresentaram atratividade "média" ou superior. As mesorregiões com maior potencial para o desenvolvimento da silvicultura foram a Região Metropolitana de Belo Horizonte, o Sudoeste de Minas e a Zona da Mata. Os segmentos de siderurgia e celulose e papel encontraram fatores de atratividade em 74,08% e 72,79% dos municípios, respetivamente. Concluiu-se que a metodologia aplicada mostrou o quanto uma localidade estava próxima de atender às características das indústrias de base florestal. Espera-se incentivar futuras pesquisas e influenciar o planejamento estratégico para a expansão do setor florestal no país.